2011
DOI: 10.5120/3056-4164
|View full text |Cite
|
Sign up to set email alerts
|

Design of PI Controller using Characteristic Ratio Assignment Method for Coupled Tank SISO Process

Abstract: This paper presents the PI controller design for coupled tank as Single Input Single Output (SISO) process using Characteristic Ratio Assignment (CRA) method.CRA is an approach to directly control the transient response of linear time invariant control systems. The transient response for all pole transfer function of n th order system can be controlled by introducing a set of parameters(α i ) characteristic ratio, (i=1,2,…,n) and ( )generalized time constant.The CRA method which satisfies more specification an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The optimal weight derived from this stage is used to generate an initial 100 population for a GA, which was run for 500 generations to obtain the optimal values of the unknown parameters of the WNN. This is a case of non-linear MIMO system, which is more challenging than most recently reported SISO in literature [8,18,28,41] , and the training approach was adopted for the following reasons in order to avoid the problem of being trapped in a local minimum solution. Moreover, it was shown after some heuristic study that the proposed is a faster approach.…”
Section: The Term δϕX δXmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal weight derived from this stage is used to generate an initial 100 population for a GA, which was run for 500 generations to obtain the optimal values of the unknown parameters of the WNN. This is a case of non-linear MIMO system, which is more challenging than most recently reported SISO in literature [8,18,28,41] , and the training approach was adopted for the following reasons in order to avoid the problem of being trapped in a local minimum solution. Moreover, it was shown after some heuristic study that the proposed is a faster approach.…”
Section: The Term δϕX δXmentioning
confidence: 99%
“…The non-linearity in the CTS is mainly due to the basic dynamic equations of the CTS, the characteristics of the valves and as a result of the nonlinear flow characteristics in the tank system [4] . Most of the literature concerned with CTSs deals with the non-linearity of the SISO system case only [8,28,29] and to the best of the authors knowledge no work has been reported in the literature indicating real-time control of the MIMO system which is recognised as being difficult to achieve. This paper uses a novel approach based on an efficient wavelet neural network (WNN) based model for an MIMO system and the design a non-linear model predictive control (NMPC) strategy for the CTS.…”
Section: Introductionmentioning
confidence: 99%